Induction of β-Lactamase Influences the Course of Development in Myxococcus xanthus - O’Connor, Kathleen A. (American Society for Microbiology, 1999)
Myxococcus xanthus is a gram-negative bacterium that develops in response to starvation on a solid surface. The cells assemble into multicellular aggregates in which they differentiate from rod-shaped cells into spherical, environmentally resistant spores. Previously, we have shown that the induction of β-lactamase is associated with starvation-independent sporulation in liquid culture (K. A. O’Connor and D. R. Zusman, Mol. Microbiol. 24:839–850, 1997). In this paper, we show that the chromosomally encoded β-lactamase of M. xanthus is autogenously induced during development. The specific activity of the enzyme begins to increase during aggregation, before spores are detectable. The addition of inducers of β-lactamase in M. xanthus, such as ampicillin, d-cycloserine, and phosphomycin, accelerates the onset of aggregation and sporulation in developing populations of cells. In addition, the exogenous induction of β-lactamase allows M. xanthus to fruit on media containing concentrations of nutrients that are normally too high to support development. We propose that the induction of β-lactamase is an integral step in the development of M. xanthus and that this induction is likely to play a role in aggregation and in the restructuring of peptidoglycan which occurs during the differentiation of spores. In support of this hypothesis, we show that exogenous induction of β-lactamase can rescue aggregation and sporulation of certain mutants. Fruiting body spores from a rescued mutant are indistinguishable from wild-type fruiting body spores when examined by transmission electron microscopy. These results show that the signal transduction pathway leading to the induction of β-lactamase plays an important role in aggregation and sporulation in M. xanthus.